Intraventricular hemorrhage as a risk factor for retinopathy of prematurity - S.V. Katsan; A.O. Adakhovska; E.S. Budivska (Ukrainian Society of Ophthalmologists, 2020)
Background: Practically any body system in the premature infant is at risk of injuries, with the leading ones being perinatal central nervous system injury and visual system injury. Purpose: To investigate the incidence of retinopathy of prematurity (ROP) in infants with intraventricular hemorrhage (IVH). Material and Methods: Eye examination records and neurosonograms of 1249 preterm infants were reviewed. All these infants underwent ROP screening in due time. The fundus was assessed as per the 2005 International Classification of Retinopathy of Prematurity (ICROP). Neurosonograms were performed on days 1 to 4, 10 to 14, and weeks 4 to 8 of life to obtain data on the presence of IVH. Intracranial intraventricular hemorrhage was classified as per ICD-10. In particular, subependymal hemorrhage (without intraventricular extension) was classified as Grade 1, and subependymal hemorrhage with intraventricular extension (bleeding into ventricle) was classified as Grade 2. In addition, subependymal hemorrhage with intraventricular extension with enlargement of ventricle was classified as Grade 3, and subependymal hemorrhage with intracerebral extension was classified as Grade 4. Statistical analyses were performed using MedCalc v.17.4 (MedCalc Software bvba, 1993-2017). Results: ROP was found in 351 infants. Of these, 65 had stage 1 ROP, 155 had stage 2 ROP, 45 had type 1 pre-threshold ROP, 28 had stage 3 ROP, 25 had threshold ROP, and 33 had aggressive posterior ROP (APROP). No ROP was found in 898 infants. Of the 1249 preterm infants, 609 had neurosonographic findings of IVH, including 406 infants with grade 1 or 2 (i.e., low-grade) IVH and 203 infants with grade 3 or 4 (i.e., high-grade) IVH. No IVH was found in 640 infants. Of the 406 infants with low-grade IVH, 58.4% had no ROP, 6.4% had stage 1 ROP, 16.5% had stage 2 ROP, 6.6% had type 1 pre-threshold ROP, 3.9% had stage 3 ROP, 2.4% had threshold ROP and 5.1% had APROP. Of the 203 infants with high-grade IVH, 63% had no ROP, 3.4% had stage 1 ROP, 20.7% had stage 2 ROP, 6.4% had type 1 pre-threshold ROP, 1.5% had stage 3 ROP, 3.4% had threshold ROP and 1.5% had APROP. Conclusion: Of the 640 infants without IVH, 82.9% were found to have no ROP, whereas of the 406 infants with low-grade IVH and 203 infants with high-grade IVH, 58.4% and 63%, respectively, were found to have no ROP. Infants with IVH had higher chances for developing ROP (OR=3.2; 95% CI, 2.5-4.2; p < 0.001). Infants with high-grade IVH had higher chances for developing particular stages and forms of ROP (stage 2 and threshold ROP) (OR=2.4; 95% CI, 1.7-3.35; p < 0.05). IVH was found to be a risk factor for developing ROP.